Witchcraft with Specific Reference to the Oracles, and Magic Among the Azande by E. E. Evans Pritchard - Shamhuna, Abdul (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This work dives into the many layers of witchcraft, oracles, and magic that shape Azande society, a theme first explored by E. E. Evans Pritchard. It isn’t just about abstract ideas; rather, the study shows how these practices mingle with everyday life and help settle disputes in unexpected ways. Using a mix of ethnographic fieldwork, first-hand documents, and historical narratives, the research doesn’t simply list evidence but paints a picture of practical community tools, sometimes overlapping in purpose. Generally speaking, the beliefs in witchcraft and reliance on oracles not only explain misfortune but also serve to knit the community together, regulating social interactions in a very tangible way. There’s also a notable impact on healthcare; these cultural practices influence how illness and healing are understood, leading to a kind of dual approach where traditional remedies coexist with modern medicine, even if the blend isn’t always seamless. In most cases, this mix offers valuable insights not only for anthropologists but also for healthcare professionals, policymakers, and researchers interested in the deep cultural roots of health and sickness among indigenous populations. Recognizing these long-held beliefs in daily life means that interventions might be better tailored to fit the cultural context of patients, ultimately fostering improved outcomes and promoting culturally competed care. Overall, the study sparks cross-disciplinary conversations about the interplay of culture and health, underlining the need for frameworks that truly value traditional practices alongside contemporary medical approaches.